Association of PD-L1 expression and clinical outcomes in ROS1 - rearranged advanced non-small cell lung cancer treated with crizotinib - Zhang, Huixian; Zhang, Ziheng; Yan, Ningning; Li, Xingya (Frontiers in Oncology, 2024)
Background: Programmed cell death ligand 1 (PD-L1) is more readily expressed in ROS proto-oncogene 1 (ROS1) rearranged non-small cell lung cancer (NSCLC) compared to NSCLC cases lacking driver gene mutations. Prior research has established a link between PD-L1 expression and reduced effectiveness of EGFR or ALK inhibitors in EGFR or ALK-positive NSCLC. Nonetheless, the relationship between initial PD-L1 levels and the clinical impact of first-line crizotinib therapy in ROS1-rearranged NSCLC is still uncertain.Methods: From January 2016 to December 2021, a total of 246 patients with ROS1 positive tumors were collected. Out of these, 82 patients with advanced ROS1-rearranged NSCLC, who were treated with crizotinib as their initial therapy, were selected for the study. The study aimed primarily to evaluate the objective response rate (ORR) and progression-free survival (PFS), and secondarily to assess disease control rate (DCR) and overall survival (OS).Results: Of the 82 advanced ROS1-rearranged NSCLC patients, 38 exhibited PD-L1 positivity, subdivided into 11 with high and 27 with low expression levels, while the 2 remaining 44 showed no PD-L1 expression. The ORR for all included patients was 80.5%. No statistically significant variance in ORR was observed among ROS1-rearranged NSCLC patients across differing PD-L1 expression statuses.However, there was a statistically significant difference in DCR between PD-L1 negative group (100%) and high expression group (90.9%) (p=0.04). The median PFS spanned 26.4 months for the PD-L1 negative group, 16.6 for the low expression group, and 13.7 for the high expression group (p=0.001). Additionally, a notable statistical disparity was also observed in median PFS between the PD-L1 negative and positive groups (p=0.02). For the entire study population, the median OS was 53.0 months (95% CI 43.8 -62.2). In the PD-L1-negative group, the median OS reached 57.2 months, compared to 53.0 months in the PD-L1-positive group, a difference lacking statistical significance (p=0.43).Conclusions: Our results suggest that for ROS1-positive NSCLC patients receiving crizotinib as first-line therapy, PD-L1 expression may serve as a negative prognostic marker for progression-free survival (PFS) rather than overall survival (OS).